A Review of Improvement on LEACH Protocol in Wireless Sensor Network - Siddiqui, Uruj Fatma; Gaurang Tiwari, Raj; Kumar, Pankaj (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor network is a network that is composed of number of non rechargeable or non replaceable sensor nodes due to its limited battery power. In WSN routing techniques energy consumption is one of the most important issue to be considered. Hierarchical routing protocols are the best known protocols to minimize the energy consumption. LEACH protocol is one the cluster based hierarchical routing protocol. LEACH increases the network lifetime by consuming small percentage of total energy dissipated in network. This paper reviews on the LEACH protocol and its descendents.